ANALISIS BEBAN KERJA DAN KEBUTUHAN KARYAWAN PEMUPUKAN KELAPA SAWIT DI PT. WIRA INOVA NUSANTARA KABUPATEN KUTAI TIMUR KALIMANTAN TIMUR - Aries Rimbawan (Politeknik Pertanian Negeri Samarinda, 2020)
This research is motivated by the growing area of ​​land or land used for oil palm business, in the industrial and cultivation sectors and in the company also has a design in determining the desired employee needs including determining the right employee needs according to their workload. emban. This study aims at workload to analyze workload, effective working time, and the amount of labor required by the fertilizer division. The study was conducted using the work sampling method to determine the pattern of activities in the use of working time. Fertilizing employees for 3 working days for each employee with an observation time interval of 10 minutes. This study uses a qualitative approach by means of observation and interviews. The results showed a job description of each employee in the fertilization section. The effective working time owned by employees is 59,976 minutes per year with effective working days for a year is 204 days. The total annual workload of the surface part is 60,384 minutes with a total of 13 employees. These results indicate that the number of employees who are deficient will have an impact on the completion time of the task. Therefore, it is advisable for the section that handles employees at PT Wira Inova Nusantara to review the distribution of employees in order to produce optimal and timely work. It is hoped that it can provide information that can be useful for those who read or who want to develop existing methods to be better and more effective methods and can be used as an evaluation in planning and determining the needs of fertilization employees for future consideration and evaluation.